2004
DOI: 10.3386/w10219
|View full text |Cite
|
Sign up to set email alerts
|

How Large are the Classification Errors in the Social Security Disability Award Process?

Abstract: This paper presents an "audit" of the multistage application and appeal process that the U.S. Social Security Administration (SSA) uses to determine eligibility for disability benefits from the Disability Insurance (DI) and Supplemental Security Income (SSI) programs. We study a subset of individuals from the Health and Retirement Study (HRS) who applied for DI or SSI benefits between 1992 and 1996. We compare the SSA's ultimate award decision (i.e. after allowing for appeals) to the applicant's self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 13 publications
(11 reference statements)
0
62
0
4
Order By: Relevance
“…The U. S. General Accounting Office (1997) Figure 4 (Rupp and Scott, 1998;Black, Daniel and Sanders, 2002;Autor and Duggan, 2003 Figure 2). Remarkably, two-thirds of these terminated claimants eventually re-qualified for DI benefits under a different impairment (Lewin Group, 1998 Gruber and Kubik (2005) '^B enitez-Silva, Buchinsky and Rust (2004) GAO, 1997, p. 43 (Weaver, Shapiro and Jacobs, 1995 600^' k3…”
mentioning
confidence: 99%
“…The U. S. General Accounting Office (1997) Figure 4 (Rupp and Scott, 1998;Black, Daniel and Sanders, 2002;Autor and Duggan, 2003 Figure 2). Remarkably, two-thirds of these terminated claimants eventually re-qualified for DI benefits under a different impairment (Lewin Group, 1998 Gruber and Kubik (2005) '^B enitez-Silva, Buchinsky and Rust (2004) GAO, 1997, p. 43 (Weaver, Shapiro and Jacobs, 1995 600^' k3…”
mentioning
confidence: 99%
“…Work disability is difficult to determine, and the SSA SSD system has been widely criticized (3,39,41,42). The SSA reported that the initial SSA allowance (approval) rate for fibromyalgia as the primary impairment was 13.9% in 2009 -2011 (40), while in 2005, 39% of all diagnoses were approved at the initial allowance level (39).…”
Section: Discussionmentioning
confidence: 99%
“…The Social Security Administration (SSA) "must ensure there is sufficient objective evidence to support a finding that the person's impairment so limits the person's functional abilities that it precludes him or her from performing any substantial gainful activity" (2). While this is never an easy task (3,4), it is particularly difficult with fibromyalgia, a contested disorder (5), and a type of illness "where sufferers claim to have a specific disease that many physicians do not recognize or acknowledge as distinctly medical" (6,7). High rejection rates may be found in complex musculoskeletal diagnoses and complex psychiatric diagnoses as compared to well-defined ones (8).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Benitez-Silva, Buchinsky, and Rust (2004) offer evidence that both types of classification errors are common in the social security disability system in the United States.…”
Section: Framework and Analysismentioning
confidence: 99%